Association between women's empowerment and infant and child feeding practices in sub-Saharan Africa: an analysis of Demographic and Health Surveys. Issue 17 (8th September 2015) - Na, Muzi; Jennings, Larissa; Talegawkar, Sameera A; Ahmed, Saifuddin
Abstract: Objective: To explore the relationship between women's empowerment and WHO recommended infant and young child feeding (IYCF) practices in sub-Saharan Africa. Design: Analysis was conducted using data from ten Demographic and Health Surveys between 2010 and 2013. Women's empowerment was assessed by nine standard items covering three dimensions: economic, socio-familial and legal empowerment. Three core IYCF practices examined were minimum dietary diversity, minimum meal frequency and minimum acceptable diet. Separate multivariable logistic regression models were applied for the IYCF practices on dimensional and overall empowerment in each country. Setting: Benin, Burkina Faso, Ethiopia, Mali, Niger, Nigeria, Rwanda, Sierra Leone, Uganda and Zimbabwe. Subjects: Youngest singleton children aged 6–23 months and their mothers ( n 15 153). Results: Less than 35 %, 60 % and 18 % of children 6–23 months of age met the criterion of minimum dietary diversity, minimum meal frequency and minimum acceptable diet, respectively. In general, likelihood of meeting the recommended IYCF criteria was positively associated with the economic dimension of women's empowerment. Socio-familial empowerment was negatively associated with the three feeding criteria, except in Zimbabwe. The legal dimension of empowerment did not show any clear pattern in the associations. Greater overall empowerment of women was consistently and positively associated with multiple IYCF practices in Mali, Rwanda and Sierra Leone. However, consistent negative relationships were found in Benin and Niger. Null or mixed results were observed in the remaining countries. Conclusions: The importance of women's empowerment for IYCF practices needs to be discussed by context and by dimension of empowerment.